Penjadwalan Crew Change Tenaga Kerja Offshore Pada Instalasi Bawah Laut Menggunakan Pendekatan CPM dan PERT - Moses, Al Varian Pradipta; Moeis, Ahmad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Offshore facilities are exploration areas that can be removed on the beach from a geographical location. Offshore facilities are located offshore and far from land with different forms of construction and very limited space for workers, so that occupational safety and health factors are a top priority in implementing For this reason, it is necessary to pay attention to the proper scheduling and equitable replacement of crew so that activities carried out at Offshore Facilities can reduce the impact of offshore worker accidents. The Critical Path Method (CPM) identifies the critical path as a series of components for the total number of activities and indicates the longest time period with the fastest project completion. The critical path starts from the first activity to the last project. The critical path is important for implementation projects. Activities that are delayed on one track will cause a delay in the project as a whole. The estimated time used in CPM is only one that represents normal time (Kholil, et al, 2018). In carrying out a management project to get the critical path, use a parallel layout which is arranged proportionally by calculating the distance traveled. If the company is able to apply the Critical Path Method (CPM) method well, then the project can be completed in the right timeframe and can help the company in planning and controlling projects with more efficient time and costs. PERT (Program Evaluation and Technology Review) is a project management technique that uses three time estimates for each activity. The three estimation numbers, namely a (optimistic timeframe), b (pessimistic timeframe), and m (most likely timeframe). By carrying out the Rescheduling Process using the CPM and PERT Approaches, it can provide information and applications to complete the ongoing project schedule and which will be carried out at a later date besides indirectly contributing to cutting costs incurred in completing the project.